1934
DOI: 10.1152/ajplegacy.1934.109.1.139
|View full text |Cite
|
Sign up to set email alerts
|

An Economy of Water in Renal Function Referable to Urea

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1

Year Published

1939
1939
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(100 citation statements)
references
References 0 publications
3
96
1
Order By: Relevance
“…The points are more widely scattered in the lower range of values for urine volume and osmolar content, probably because urine volume is more apt to be determined by its urea content at these lower rates of salt and glucose excretion. As has been shown in the rat (9) with salt and glucose. Our data suggest that the human kidney behaves toward salt, glucose, and urea in a manner similar to that of the rat.…”
Section: Plan Of Studysupporting
confidence: 66%
“…The points are more widely scattered in the lower range of values for urine volume and osmolar content, probably because urine volume is more apt to be determined by its urea content at these lower rates of salt and glucose excretion. As has been shown in the rat (9) with salt and glucose. Our data suggest that the human kidney behaves toward salt, glucose, and urea in a manner similar to that of the rat.…”
Section: Plan Of Studysupporting
confidence: 66%
“…Urea's importance has been appreciated for nearly 8 decades, since Gamble et al first described "an economy of water in renal function referable to urea" (19). Protein deprivation reduces maximal urine concentrating ability and is restored by urea infusion or correction of the protein malnutrition (11,16).…”
Section: Urine Concentrating Mechanismmentioning
confidence: 99%
“…Urea's importance to the generation of a concentrated urine has been appreciated since at least 1934. 1,2 Several studies have shown that maximal urine concentrating ability is decreased in protein-deprived mammals and is restored by urea infusion. 3 More recently, a UT-A1/UT-A3 knock-out mouse, 4,5 a UT-A2 knock-out mouse, 6 and a UT-B knock-out mouse [7][8][9] were each shown to have urine concentrating defects.…”
mentioning
confidence: 99%